Model Predictive Control of a BCDFIG With Active and Reactive Power Control Capability for Grid-Connected Applications - R. Rezavandi; D. A. Khaburi; M. Siami; M. Khosravi; S. Heshmatian (Iranian Journal of Electrical and Electronic Engineering, 2021)
Recently, Brushless Cascaded Doubly Fed Induction Generator (BCDFIG) has been considered as an attractive choice for grid-connected applications due to its high controllability and reliability. In this paper, a Finite Control Set Model Predictive Control (FCS-MPC) method with active and reactive power control capability in grid-connected mode is proposed for controlling the BCDFIG in a way that notable improvement of the dynamic response, ripple reduction of the active and reactive power waveforms and also better THD performance are achieved compared to the traditional approaches such as Vector Control (VC) method. For this purpose, the required mathematical equations are obtained and presented in detail. In order to validate the proposed method performance, a 1–MW grid-connected BCDFIG is simulated in MATLAB/Simulink environment.